P4.107 Parents Child Communication Improvement Among HIV Infected & Affected Children. (13th July 2013) - Das(Konar), S; Panda, N; Kundu, M; Chowdhury, S; Sonkar, R; Basu, R; RoyChowdhury, A
Abstract : One of the major impacts of the HIV & AIDS epidemic on global society is seen in the increase number of children being infected & affected by AIDS. There is a need for one programme to addressing these issues to support of those children & their parents who are suffering from AIDS. CINI was working on 300 children & their parents of IICCHAA project since 2006. The memory work sessions taught the parents and children to accept reality and cope to live in their own surrounding by using their creative minds to open up opportunities of self-discovery and self- sustaining. In these sessions, children and parents started to share by transparent communication with families, providing care and support, unified planning for future by taking everybody's opinion and views according to their needs. CINI assessed this programme in two levels -Developing the resilience of the Children andEmpowerment of the children. 300 children & their parents/family members were empowered through memory work sessions. A comparative analysis of the current situation shows that: The ratio of Communication skill has been increased from 17.3% to 80.5% The leadership qualities boosted from 12% to 72% The Children developed themselves for taking care of parents, earlier the ratio was 9% which is raises up to 57% Parents are becoming empowered to disclose their status. Presently the percentage increases from 15 to 90 Earlier the Parents were not able to prepare any succession plan for safe guard of their children. At present it is developed up to 97% The PLHIVs can improve the quality of their lives, if IICCHAA will include in the national programme.